Radix Pseudostellariae protein-curcumin nanocomplex: Improvement on the stability, cellular uptake and antioxidant activity of curcumin. (May 2021) - Cai, Xixi; Weng, Qingxia; Lin, Jiaming; Chen, Guiqing; Wang, Shaoyun
Abstract: Radix Pseudostellariae protein (RPP) with satisfactory antioxidant activity and self-assembled ability was extracted from dried Radix Pseudostellariae . In this study, RPP-curcumin nanocomplex (RPP-Cur) was fabricated, and its improvement on the stability, cellular uptake and antioxidant activity of curcumin was investigated. RPP-Cur with homogeneously spherical structure exhibited good stability, which could maintain the morphology against simulated gastrointestinal digestion and up to 300 mM ionic concentration. After RPP nanoparticles encapsulation, the retention of curcumin increased 1.45 times under UV irradiation for 6 h. Besides, RPP-Cur exhibited additive reducing power of curcumin and RPP. The transport efficiency of hydrophobic curcumin across Caco-2 cells monolayer was greatly improved by RPP nanoparticle by 3.7 folds. RPP-Cur was able to be internalized by Caco-2 cells dose-dependently via macropinocytosis and clathrin-mediated endocytosis. The cellular uptake efficiency of embedded curcumin in RPP nanoparticles by Caco-2 cells was significantly higher than that of free curcumin, which might contribute to the enhanced intracellular antioxidant activity of RPP-Cur. These findings suggest that the proteins from Radix Pseudostellariae have potential to be developed into novel delivery system with intrinsic antioxidant activity for the hydrophobic active molecules in healthy food field. Graphical abstract: Image 1 Highlights: Curcumin in RPP-curcumin nanocomplex (RPP-Cur) showed better stability against UV exposure. RPP-Cur exhibited additive reducing power of curcumin and RPP. RPP-Cur greatly improved the transport efficiency of curcumin across Caco-2 cells monolayer. The intracellular antioxidant activity of curcumin were enhanced by RPP-Cur.